The Literature Review on UTAUT 2: Understanding Behavioral Intention and Use Behavior of Technology in the Digital Era - Yuliani, Pande Nyoman; Suprapti, Ni Wayan Sri; Widagda K., I GN Jaya Agung; Piartrini, Putu Saroyini (International Journal of Social Science and Business, 2024)
In the rapidly developing digital era, technology has become an indispensable aspect of human life, and has penetrated various fields including work, education and lifestyle. Understanding behavioral intentions and technology use behavior has become an important endeavor for individuals and organizations. In response, researchers have developed a variety of models to analyze this behavior, with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) as a comprehensive theoretical framework. This review investigates UTAUT 2 based on research published between 2012 and 2024, exploring its significance in deciphering the complexities of technology adoption in the digital era. By examining factors such as performance expectancies, effort expectancies, social influences, facilitating conditions, hedonic motivation, price values, and habits, this review explains their influence on individual decision making. In addition, it evaluates empirical research, addresses emerging criticism, and explores recent advances, aiming to contribute to the advancement of knowledge in technology acceptance. Despite its advantages, UTAUT 2 faces challenges such as contextual adaptation and predicting dynamic behavior. Nevertheless, the future of this technology remains promising as research efforts continue to refine and expand its application in navigating the ever-evolving digital landscape.